(3GdESJTGQGJ GdGOGQjI (B/s - (3GdMejQj, HGSes ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2010)
(3eONd Gdi GdGSJTGQGJ (B-(3MGLGJ GdRhHhf GdGSJTGQj(B- (3HOGjGJ GdegeI GdGSJTGQjI (B- (3eQGMd GdYedjI GdGSJTGQjI , GdGJUGd GdaYGd HGdRHhf (B-(3JWhjQ bGHdjGJ GdGSJTGQj(B- (3eYhbGJ GdYed GdGSJTGQj(B- (3GdGSJTGQj GdOGNdj (B.s
(3eQGLY U(B.196(3; edGMb U(B.183s
Keywords: (3EOGQI GdGYeGds; (3GdESJTGQGJ GdEOGQjIs; (3GdJfejI GdEOGQjIs